As concepções da formação profissional da licenciatura em educação física: trajetórias docentes e suas perspectivas contributivas - Krüger, Leonardo Germano (2007)
This abstract of research is included in the line of research Formation, Knowledge and professional development (PPGE/CE/UFSM). The objective of this investigation was to understand the teaching of conception of new Physical Education Graduate of the CEFD/UFSM go away instruction trajectory of teachers involved in the construction process and introduce of the politician-pedagogical project and course reorganization of the year of 2004 (CEIPPP/RC). The methodology characterized as qualitative of the type case study. They had participated of the representative inquiry four teacher-personage of the CEIPPP/RC, which, through the verbal narrative had carried through its stories. Beyond the narratives it was possible to have access to the politician-pedagogical project and of Acts registered during the meeting of the CEIPPP/RC. For the analysis of the information it searched identification of the thematic focus through the technique of the gradual reduction of the text. In this direction, the narratives had assumed a biographical character of as the professors if they show when they speak of itself, of the profession and the context, what it allowed to seat the formation and its conceptions in its trajectory of life. The categories constructed from the narrative of the professor-personage express its conceptions, which if identify with the holistic and ecological vision that praises the politician-pedagogical project: the awareness in assuming the construction of an interlaced educative project with the agreement of that the with regard to process is capable to produce changes from new learnings, which had been perceived as reflected of the proper performance of itself during the process of construction of the PPP and the curricular reorganization. Thus, it was important to observe as the distinct moments practice for the professor-personage in its formative trajectory had influenced them in the construction of its conceptions, having been considered, therefore, as personage of our inquiry because they had been citizens of proper history that had counted